2008
DOI: 10.1002/ajh.21325
|View full text |Cite
|
Sign up to set email alerts
|

Familial myeloma and monoclonal gammopathy: A report of eight African American families

Abstract: Previous descriptions of familial myeloma have been mainly of Caucasian families. We report here eight African American families with familial multiple myeloma and monoclonal gammopathy identified over a 30 year period. Six patients with multiple myeloma (MM) and two with monoclonal gammopathy of unknown significance (MGUS) reported a family history of MM or had family members with MGUS found on screening. A pedigree compiled for each family included a history of other cancers. In the eight families, 21 of 58 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Lynch et al 33 described an African-American family with five cases of MM, three case of MGUS and five cases of prostate cancer among 11 first-degree relatives. Jain et al 34 reported on eight African-American families with familial MM and MGUS seen in a 30-year period at a single institution. A total of 21 of 58 first-degree relatives had a plasma cell dyscrasia including 12 MM, eight MGUS and one amyloidosis.…”
Section: Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lynch et al 33 described an African-American family with five cases of MM, three case of MGUS and five cases of prostate cancer among 11 first-degree relatives. Jain et al 34 reported on eight African-American families with familial MM and MGUS seen in a 30-year period at a single institution. A total of 21 of 58 first-degree relatives had a plasma cell dyscrasia including 12 MM, eight MGUS and one amyloidosis.…”
Section: Yearsmentioning
confidence: 99%
“…Additional malignancies were found 21 other family members, most commonly leukemia, lymphoma and myeloproliferative disorders (n ¼ 5), breast cancer (n ¼ 4), prostate cancer (n ¼ 3) and colon cancer (n ¼ 3). 34 …”
Section: Yearsmentioning
confidence: 99%
“…Another investigation focused on examining the pedigrees of 6 African American patients with MM and 2 with MGUS. 12 Of the 58 first-degree blood relatives, 21 were found to have a plasma cell disorder (12 MM, 8 MGUS, 1 amyloidosis; Table 1). Despite the small sample size in both of these studies and lack of comparison groups, both indicate possible underlying genetic factors that could play a role in susceptibility in African American populations.…”
Section: Epidemiology Of Familial Mgus and MMmentioning
confidence: 99%
“…MM has been known to be a disease of older adults, where the median age at diagnosis is 66 years. Only 10 percent are younger than 50 years, and a mere 2 percent of patients are younger than 40 years [6, 7]. …”
Section: Introductionmentioning
confidence: 99%